Aluminum Insertion‐Induced Enhanced Performance of Li(Ni0.83‐xCo0.10Mn0.07Aly)O2 Microspheres for Lithium‐Ion Batteries Design. Issue 3 (5th December 2013) - Chen, Weihua; Zhao, Juanjuan; Li, Yanyang; Li, Shao; Jin, Chuanchuan; Yang, Changchun; Feng, Xiangming; Zhang, Jianmin; Mi, Liwei
Abstract An effective and facile strategy to synthesize spherical Li(Ni0.83‐xCo0.10Mn0.07Aly)O2 with a metal concentration gradient is presented. Spherical‐shaped Ni0.83Co0.10Mn0.07(OH)2 with hierarchical microstructure is used as the precursor. Al3+ inserts into Ni0.83Co0.10Mn0.07(OH)2 by replacing Ni2+ in Ni0.83Co0.10Mn0.07(OH)2 microspheres, resulting in a gradient distribution of Al and Ni within the microspheres. The Ni concentration decreases linearly, whereas the Al concentration increases linearly from the center to the outer layer of each particle. However, the distribution of Mn and Co is nearly uniform throughout the whole particle. This result is verified by using energy‐dispersive X‐ray mapping, line scanning, and inductively‐coupled plasma spectrometry. Electrochemical tests are carried out by using the as‐synthesized samples as positive‐electrode materials in lithium‐ion batteries. Results show that the discharge capacity, cyclability, and rate performance of these samples are clearly enhanced with respect to those of the untreated sample. The specific discharge capacity of the obtained sample at a discharge current of 0.1 C reaches 203.4 mAh g−1, whereas the modified material depicts a much higher specific capacity of 141.7 mAh g−1 during the 30th cycle, compared with only 80.8 mAh g−1 for the untreated sample. In addition, a series of materials with different Ni/Al ratios are synthesized by using this approach, for which the adjusted reaction parameters also affect their electrochemical properties. This simple synthetic strategy may be extended to construct nano‐/microsized particles with concentration gradients, offering new opportunities to study the composition‐dependent phenomena at the nano‐/microscale, as well as to provide a way of tuning the chemical/physical properties.